2016
DOI: 10.1111/neup.12299
|View full text |Cite
|
Sign up to set email alerts
|

C11orf95‐RELA fusion present in a primary intracranial extra‐axial ependymoma: Report of a case with literature review

Abstract: Ependymomas are gliomas that recapitulate the ependymal cells microscopically and ultrastructurally. They commonly occur along the ventricular surfaces and central canal of the brain and spinal cord. Intracranial extra-axial ependymoma (IEAE) is a rare entity and is commonly misdiagnosed clinically and radiologically as a meningioma. The histogenesis of such IEAEs is obscure. A novel recurrent oncogenic fusion involving the C11orf95 and RELA genes was recently described in supratentorial ependymomas. A 9-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The K27M in H3F3A is a major mutation found in diffuse midline gliomas [22-25]. Additionally, a C11orf95-RELA fusion was found in supratentorial ependymomas [26-34]. A V600E mutation in BRAF was found in circumscribed gliomas, such as pleomorphic xanthoastrocytoma (PXA) (66%) [35-38], gangliogliomas (25%) [35,38], and pilocytic astrocytomas (15%) [35,38].…”
mentioning
confidence: 99%
“…The K27M in H3F3A is a major mutation found in diffuse midline gliomas [22-25]. Additionally, a C11orf95-RELA fusion was found in supratentorial ependymomas [26-34]. A V600E mutation in BRAF was found in circumscribed gliomas, such as pleomorphic xanthoastrocytoma (PXA) (66%) [35-38], gangliogliomas (25%) [35,38], and pilocytic astrocytomas (15%) [35,38].…”
mentioning
confidence: 99%
“…However, a few studies have reported favorable outcomes in patients diagnosed with RELA fusion-positive ependymoma and who had undergone with gross total resection [ 17 , 18 ]. C11orf95-RELA fusion gene was previously reported in one SEAE case with a history of 6-month follow-up and no recurrence [ 10 ]. The present case with the same fusion gene detected had two recurrences during the postoperative follow-up period of 1 and 4 years, and the patient died 4 months after the second recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] 43, F Lt posterior one-third parasagittal/7.2 × 5.9 × 4 Meningioma (meningioma, favor) GTR Classical Ep/II RT 6 NR 5 Nambirajan et al . [ 10 ] 9, F Rt frontal parafalcine/NA Meningioma Hemangiopericytoma GTR Anaplastic, focal clear-cell, Ep/III RT 6 NR C11orf95-RELA fusion gene (+) 6 Yang et al . [ 11 ] 47, M Lt middle-third parafalcine/3.8 × 3.2 × 2.1 Meningioma GTR Anaplastic Ep/III RT 53 NR Preoperative gamma knife radiosurgery 7 Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…About 70% of cases of supratentorial ependymomas are characterized by RELA-C11orf95 fusion and 30% by YAP1 gene fusion [ 43 , 77 ]. It is known that the LAMA2 overexpression group show worse prognosis than NELL2 overexpression group among the cases of posterior fossa ependymomas [ 1 , 46 ].…”
Section: Genetic Abnormalities In Pediatric Gliomasmentioning
confidence: 99%
“…The partner gene can be a gene other than C11orf95. The grade of this tumor follows a pathologic grade that is evaluated according to existing morphologic features, but the prognosis is worse in the case of RELA fusion than YAP fusion [ 43 , 51 ].…”
Section: Genetic Abnormalities In Pediatric Gliomasmentioning
confidence: 99%